ASSESSMENT OF RADON CONCENTRATION AND ASSOCIATED HEALTH IMPLICATIONS IN GROUND WATER AND SOIL AROUND RIRUWAI MINE SITE, KANO STATE, NIGERIA AND ITS ENVIRONS (FUDMA JOURNAL OF SCIENCES, 2020)
In this study 10 soil and 11 ground water samples were randomly collected, and the 222Rn concentrations were measured using a DURRIDGE RAD7 electronic radon detector. The radon concentration in ground water ranged from 0.53 BqL-1 to 5.13 BqL-1 with a mean value 2.37 BqL-1. The results show that all the groundwater samples collected have 222Rn concentrations below the US EPA Maximum Contaminant Level (MCL) of 11.1 BqL–1 (for states without radon monitoring policy and enhanced indoor air programs). All the ground water samples also have 222Rn concentrations below MCL of 100 BqL–1 recommended by EU. The annual effective dose due to ingestion (Hing) of 222Rn in the groundwater ranged from 0.00386 – 0.03744 mSvyear-1 with a mean value of 0.01706 mSvyear-1. These values are within the ICRP recommended reference level of 1 mSvy–1 for the intake of the radionuclide in water by the general public for a prolonged exposure. The effective radium content, radon mass exhalation rate and alpha index of the soil samples varied from 0.574 – 1.170 Bqkg-1, 0.104 Bqkg-1d-1 – 0,212 Bqkg-1d-1 and 0.00287 – 0.00585 respectively. The alpha index suggests that none of the selected soil samples have a radon mass exhalation that could cause indoor radon concentrations exceeding 200 Bqkg-1. Therefore, it is concluded that the radon concentration in ground water and soil in the study area indicate that the ground water is safe for drinking and it is safe to use the soil as a building material.
Keywords: Radon, Ground water, Soil, Exhalation Rate, Annual Effective Dose